VEGF as a Predictor of Mitotic Activity and Brain Invasion in Meningioma - Pajan, Hendra Fajar; Widodo, Djoko; Miskad, Upik Andriani; Hendarto, Joko; Islam, Andi Asadul; Christian Oley, Maximillian; Faruk, Muhammad (Asian Pacific Journal of Cancer Biology, 2025)
Background: Meningiomas exhibit variable biological behavior, with mitotic activity and brain invasion being critical histopathological markers of aggressiveness. While Vascular Endothelial Growth Factor (VEGF) is implicated in tumor progression, its precise role in driving these specific aggressive features in meningioma remains to be fully elucidated. This study investigated the association between immunohistochemical VEGF expression, mitotic activity, and brain invasion in meningioma. Methods: We conducted a retrospective, cross-sectional analysis of 73 surgically resected meningioma specimens. VEGF expression was semi-quantitatively scored via immunohistochemistry (negative, weak, moderate, strong) and correlated with mitotic counts (per 10 high-power fields, HPF) and the presence of brain invasion. Associations were assessed using the chi-square test. Results: High VEGF expression was significantly associated with a higher mitotic index (≥4 mitoses/10 HPF) (p=0.005); notably, 80% (8/10) of cases with high mitotic activity demonstrated moderate to strong VEGF expression. Furthermore, VEGF expression was significantly elevated in brain-invasive meningiomas compared to their non-invasive counterparts (p=0.007), with 75% (3/4) of invasive cases exhibiting strong VEGF expression. Conclusion: Elevated VEGF expression strongly and statistically significantly correlates with both increased mitotic activity and brain invasion in meningiomas. These findings underscore VEGF’s crucial role as a mediator of tumor proliferation and parenchymal infiltration, positioning it as a potential biomarker for aggressive meningioma and a promising target for future therapeutic interventions.